2020
DOI: 10.1016/j.nicl.2020.102340
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem 7 Tesla MRI detection of white matter hyperintensities: A multidisciplinary voxel-wise comparison of imaging and histological correlates

Abstract: Highlights Ultra high-field post mortem MRI is a valid tool for the study of white matter hyperintensities. Demyelination and parenchymal rarefaction are associated with FLAIR and T2 changes on 7 Tesla MRI. Age, length of fixation and pathological diagnosis are all significant predictors of white matter FLAIR voxel intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…All scans of postmortem tissue were performed at Western's Centre for Functional and Metabolic Mapping on a 7T Scanner (Siemens) following a previously described imaging protocol [ 33 ]. Briefly, frontal coronal sections were selected from each fixed brain and immersed in Galden HT‐270 perfluorinated fluid in a custom‐stacking device for imaging.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All scans of postmortem tissue were performed at Western's Centre for Functional and Metabolic Mapping on a 7T Scanner (Siemens) following a previously described imaging protocol [ 33 ]. Briefly, frontal coronal sections were selected from each fixed brain and immersed in Galden HT‐270 perfluorinated fluid in a custom‐stacking device for imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Determining vascular contributions to pvWMH on MRI imaging may be aided by the presence of periventricular infarcts (PVI) within the hyperintense tissue. Higher imaging resolution caused by advancements in MRI field strengths can detect small lesions of ischemic nature within pvWMH [ 33 ]. We have previously reported that the presence of these fluid filled cavities in brains with cerebrovascular disease are a significant contributor to the hyperintense signal in both the surrounding lesion and normal‐appearing white matter [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, white matter changes are detected using magnetic resonance imaging (MRI) using T2 weighted fluid attenuated inversion recovery (FLAIR), appearing as white matter hyperintensities (WMH). The etiology and development of WMH are heterogeneous, but usually involve a loss of myelin and axon density, the primary end-stage pathological correlates of WMH [25]. Within both gray and white matter, glial cells present critical targets for therapeutic intervention and neuroprotection [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…One theory of WMH development suggests that early in disease pathology, venous collagenosis 10 and increased blood brain permeability 11 cause increased local interstitial fluid. This increased interstitial fluid then triggers a pathological cascade to glial (including oligodendroglial) and neuronal cells leading to demyelination and axonal damage 12,13 . Early interstitial fluid accumulation is potentially reversible, but usually the trend is for progression towards irreversible myelin loss and neuronal damage 8 .…”
Section: Introductionmentioning
confidence: 99%